MENINGKATKAN INNOVATION PERFORMANCE : MELALUI ABSORPTIVE CAPACITY, KNOWLEDGE MANAGEMENT CAPABILITY, DAN GENERATIONAL DIVERSITY - Ayu Laila Afifah; Budhi Cahyono (Jurnal Ekonomi dan Bisnis, 2020)
This study aims to analyze the capacity of family micro, small and medium enterprises (MSMEs) to absorb and manage relevant information from their immediate environment, and incorporate it into their innovative activities. This research also seeks to improve our understanding of the role of diversity in the generation of corporate management. This research was conducted on 126 family MSME owners in Central Java Province who are respondents with criteria that have been operating for 2 years or more and are managed by family members. The type of data in this study was obtained from primary data. Primary data obtained directly from the main source by filling out questionnaires in the form of online (google form) distributed through MSME communities and offline (print out sheets) by visiting the location of MSME families. Data analysis method used in this study is Partial Least Square (PLS) with the help of SmartPLS 3.0 software. The results showed that there was a significant positive effect on absorptive capacity on innovation performance and knowledge management capability in family MSMEs, while the role of generational diversity (multi-generation) did not have a moderating effect in strengthening the relationship between absorptive capacity and innovation performance.